AEROBIC CAPACITY AND ITS RELATIONSHIP TO FEMALE STUDENTS’ ARTISTIC GYMNASTICS PERFORMANCE - Abduljabbar Aboob, Dr. Marwa; Shamkhi Alfartosy, Dr. Rasool Mohi (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
Sports, in their various games and practices in the world, are considered the true standard for the majority of the developed countries of the world. Indeed, some countries have relied on them greatly, and sports are a great sign of the renaissance of those countries. The sport of artistic gymnastics is considered one of those basic sports for its renaissance, and the sport of gymnastics is considered one of the sports. Important, fun and interesting sports games, especially the Olympic Games and World Championships, where we noticed the development in the decline of these sports, and this came as a result of scientific progress in various areas of life, especially sports. Since advanced and modern physiological studies have increased the interest of the majority of specialists in physical education, especially artistic gymnastics, most of the modern physiological research and studies have confirmed this. The current study aimed to identify the aerobic capacity of the first-stage female students in the Department of Physical Education and Sports Sciences - Ahl al-Bayt University, as well as to identify the performance of the front roll skill among the first-stage female students, as well as to identify the relationship between aerobic capacity and the front roll performance of the first-stage female students - Ahl al-Bayt University. The research hypothesis was it can be concluded with statistical significance that there exists a relationship between aerobic capacity and front roll performance for first-stage female students. The research population was made up of first-stage female students, numbering (15 female students) for the morning study, which the researchers chose in an intentional manner. As for the research methodology, it was determined by the descriptive method to suit the chosen nature of the research. By the two researchers.